2007
DOI: 10.1111/j.1610-0387.2007.06489.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of psoriasis therapy with etanercept in Germany

Abstract: According to internationally accepted levels of cost-effectiveness thresholds, the intermittent treatment of (moderate to) severe plaque-type psoriasis with etanercept is a cost-effective measure within the German healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 23 publications
0
33
0
2
Order By: Relevance
“…It affects 1–3% of the population worldwide [6]. Recent data on the care of this disease show that psoriasis is of considerable socio-economic [7,8,9,10,11], social [12,13,14,15,16,17] and medical importance [18,19,20,21]. The scientifically recognized standard of medical care is defined by the German national treatment guideline [22].…”
Section: Health Services Research In Psoriasismentioning
confidence: 99%
“…It affects 1–3% of the population worldwide [6]. Recent data on the care of this disease show that psoriasis is of considerable socio-economic [7,8,9,10,11], social [12,13,14,15,16,17] and medical importance [18,19,20,21]. The scientifically recognized standard of medical care is defined by the German national treatment guideline [22].…”
Section: Health Services Research In Psoriasismentioning
confidence: 99%
“…Over 90 % of the studies reported objectives (item 1), sources of variable estimates (item 3), methodology of data abstraction (item 7), primary outcome measures (items 10 and 11), and choice of economic model (item 13) ( Table 1). Only five studies conducted a subgroup analysis (item 4), either based on the patients with different disease severity levels at baseline [43,56,59,67] or among patients who completed the study [65]. Approximately 40 % of the studies only estimated the cost-effectiveness ratios (e.g.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Three studies mapped the Dermatology Life Quality Index (DLQI) to European Quality of Life-5 Dimensions (EQ-5D) utilities [35,57,59]; however, Woolacott et al [67] mapped the change in DLQI associated with different PASI response categories and baseline DLQI scores to changes in EQ-5D utility. The remaining studies either estimated utility values directly from study patients [22,26,58], stated utility values from previous studies were used without providing further details [43,56], or obtained utilities by response status defined by neither PASI nor DLQI from previous studies [60].…”
Section: Synthesis Of Cost-effectiveness Analysis Studiesmentioning
confidence: 99%
“…Bald wurde ein unspezifisches ZytokinRelease-Syndrom, teilweise schon bei der ersten Infusion beobachtet, das in Fieber, Nausea und Exanthemen bis hin zu Multiorganversagen resultierte [1]. Die zunehmende Anwendung von sogenannten Biologika bei Tumoren, Autoimmunkrankheiten und entzündlichen Erkrankungen wie der Psoriasis [2,3] wirft sowohl Fragen der Sicherheit als auch der Ökonomie [3] auf. Die rasche Entwicklung neuer Biologika und die Ausweitung der Indikationen, die auch einen zunehmenden Off-Label-Use, z.…”
Section: Introductionunclassified
“…Bald wurde ein unspezifisches ZytokinRelease-Syndrom, teilweise schon bei der ersten Infusion beobachtet, das in Fieber, Nausea und Exanthemen bis hin zu Multiorganversagen resultierte [1]. Die zunehmende Anwendung von sogenannten Biologika bei Tumoren, Autoimmunkrankheiten und entzündlichen Erkrankungen wie der Psoriasis [2,3] Abbildung 1: Vorgeschlagene Klassifikation unerwünschter Arzneimittelwirkungen auf Biologika (modifiziert nach [7,8]). Bei oft nicht gesichertem Pathomechanismus (z.…”
unclassified